Pouvoir et magie de la comédie dans L’Illusion comique de Corneille - Bonolas, Philippe P. (Romanica Silesiana)
Although Corneille drew fame from his tragedies, he launched his career by writing comedies. Considered for a long time as less worthy of attention, they have been reconsidered since the end of the nineteenth century and some of them like the Illusion comique have been regularly performed and praised as a good example of French baroque theatre. In Corneille’s time, the success of a play was due to its freshness and modernity exploiting various themes favoured by the Age of Louis XIII. A play within a play was not entirely new, but mingling the intrigue of a tragedy within a more general one of a comedy was uncommon. Introducing the role of a magician, Alcandre, able to play with the dimensions of space and time when the three rules of unity began their magisterial reign, was an audacious expression of creative liberty. Besides, Corneille epitomized the baroque metaphorical vision of the world by insisting on the aspects of its instability, putting its personages in constant psychological and physical motion and metamorphosis, situations leading at times to uncertainty about moral values. But throughout the play, the theatre appears progressively as a metaphorical rationalisation of this instability through the adventurous life of the main hero, Clindor, allowing the author through Alcandre’s voice to advocate the cathartic power of comedy and assert the social importance and legitimate place of the theatre in the 17th century France. After the Illusion comique, the theatre could clearly be perceived as a school of humanism. Key words: Corneille’s theatre, baroque, comedy, a play within a play.